2022
DOI: 10.1186/s12877-022-03417-5
|View full text |Cite
|
Sign up to set email alerts
|

How formal caregiver’s BPSD knowledge influences positive aspects of caregiving: the mediating role of attitude and the moderating role of self-efficacy

Abstract: Background The current study investigated the relationship between behavioural and psychological symptoms of dementia (BPSD) knowledge and positive aspects of caregiving (PAC), in addition, how caregiving attitude and self-efficacy mediate or moderate this relationship. Methods Two hundred twenty-nine formal caregivers (51males and 178females) who has worked in nursing homes for more than a month were recruited.With a cross-sectional, face-to-face … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…Considering the direct moderate effect of self-e cacy to the knowledge improvement [35], it could be suggested that an adaptive learning-based BPSD education, which this study showed signi cantly increased both knowledge, and self-e cacy, is an appropriate direction for future LTCF education.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…Considering the direct moderate effect of self-e cacy to the knowledge improvement [35], it could be suggested that an adaptive learning-based BPSD education, which this study showed signi cantly increased both knowledge, and self-e cacy, is an appropriate direction for future LTCF education.…”
Section: Discussionmentioning
confidence: 81%
“…That the rst course, which dealt mainly with BPSD knowledge, had the highest adaptation rate, could indicate that the knowledge level of the learners in the experimental group was improved more effectively by their ability to selectively focus on the areas in which they lacked knowledge. Many previous studies have emphasized the importance of nursing staff staying up-to-date on knowledge that affects their practice, especially those who apply that practice at the very close side of residents with dementia, reporting that it leads to a positive attitude, reduced burden, and better care ability [12,35,36].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Empathy and caregivers' positive emotional experiences seemed to foster self‐efficacy, reflected in their competence and confidence in applying PCCS and caring for residents. Greater self‐efficacy supports positive aspects of caregiving such as feelings of mutuality, personal growth and purpose, and job satisfaction 57,58 and reduces the burden of care 59 . Caregivers' positive emotional experiences are vital in their provision of individualised care and personal relation to the resident 60 .…”
Section: Discussionmentioning
confidence: 99%
“…As reported previously, knowledge-based education alone is insufficient to improve care practices for PLWD (Gkioka et al, 2020;Surr & Gates, 2017). An approach to improve the attitudes of healthcare staff towards PLWD should be included in educational interventions because staff members with more positive attitudes are more likely to engage in activities and social interactions with PLWD, possibly improving person-centred care (PCC) (Hu et al, 2022;Lintern, 2001).…”
Section: Introductionmentioning
confidence: 99%